Health visiting in the UK in light of the COVID-19 pandemic experience (RReHOPE): a realist review protocol - King, E; Gadsby, E; Bell, M; Duddy, C; Kendall, S; Wong, G (BMJ, 2023)
Introduction Health visiting services, providing support to under 5s and their families, are organised and delivered in very different ways in different parts of the UK. While there has been attention to the key components of health visiting practice and what works well and how, there is little research on how health visiting services are organised and delivered and how that affects their ability to meet their objectives. The COVID-19 pandemic rapidly disrupted service delivery from March 2020. This realist review aims to synthesise the evidence on changes during the pandemic to identify the potential for improving health visiting services and their delivery.